Clinical Placements: The Perspectives of UK Physiotherapy Students on How Prepared they were by their University for their First Clinical Placements: an example of one HEI. (2014) - Thomson, Di; Boyle, Daniel; Legg, Christopher; Owen, Mathew; Newman, Melanie; Cole, Mary-Jane
No abstract available